Identifikasi Ekspektasi Investor melalui Kebijakan Struktur Modal, Profitabilitas, Ukuran Perusahaan dan GCPI - Haryanto, Sugeng (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2014)
The objective of the study was to analyze the causality influence among capital structure policy, firm size, profitability which was measured by ROA and the implementation of GCG which was measured by Good Corporate Perception Index (GCPI) toward the investors expectations which was measured by the company value. It was a purposive sampling study. The samples of this study were go public companies listed on the Indonesias Most Trusted Companies. The period of the study was in 2012 and 2013, and financial reports from 2012 to 2013. The total samples were 48 companies. The data were analyzed by multiple linear regressions. The result of the study showed that the capital structure policy and firm size did not give any influence, whereas the profitability and GCPI gave influence toward the investors expectations. Furthermore; capital structure policy, firm size, profitability and GCPI variables influenced simultaneously toward investors expectations.